LITERATURE STUDY: COMPARISON OF QUALITY OF LIFE OF OSTEOARTHRITIS PATIENTS BEFORE AND AFTER TOTAL KNEE REPLACEMENT OPERATION - Sukma Tri Andarwati; Franklin Vincentius Malonda; Oscar Indra Kusuma (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2023)
Background: Osteoarthritis (OA) of the knee is a chronic disease caused by the degeneration of the knee joint, which causes inflammation that triggers excessive pain and interferes with daily activities. According to the World Health Organization (WHO), osteoarthritis is one of the main factors that lead to a decrease in the function of a person's quality of life in the world. The choice of therapy for patients with severe osteoarthritis can be given total knee replacement surgery to treat patient complaints, especially in the aspect of excessive pain. Assessing and knowing disorders of the knee joint and the quality of life of patients with osteoarthritis before and after total knee replacement surgery can be assessed by scoring knee injury and osteoarthritis outcome scores.Objective: To compare patients' quality of life before and after total knee replacement surgery.Methods: This study uses a literature study method, journals obtained from searches using certain keywords within the last ten years.Results: The literature study found that eight journals had similarities with the research topic on the research objectives and ten journals had similarities with the research topic using a questionnaire research instrument. The study results in ten kinds of literature follow the hypothesis on the research topic, which shows a comparison of the quality of life in osteoarthritis patients before and after total knee replacement surgery.Conclusion: In ten works of literature, it can be concluded that there is a comparison of the quality of life of osteoarthritis patients before and after total knee replacement surgery. There is also a study of clinical and functional outcomes of total knee replacement.